TO THE PROBLEM OF FORMATION OF VALUABLE PERCEPTION OF ART AT FUTURE MUSIC TEACHERS IN THE PROCESS OF VOCAL AND CHORAL PREPARATION - Чжан, Бо Бо (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is sanctified to the analysis of ways of research of problem of forming of the valued perception of art for future music masters in the process of vocally-choral preparation. It is exposed features and specific of vocally-choral work. In the article attention applies on understanding of category of perception in the aspect of the creative thinking - analytical, that directs situation experiencing-perceptions the students of collisions of vocally-choral process to the argued conclusions generalized. The features of the valued perception are in-process examined by the students of maintenance of vocally-choral preparation in the aspect of creative activity of student, purposefulness, productive creative thinking, independent position in the decision of vocally-choral tasks